The vegetation of the the Bátorliget mire reserve and its changes in the last 15 years - Tinya, Flóra; Tóth, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2005)
The Bátorliget Mire Reserve is located 15 km East of the city Nyírbátor in the Nyírség Region, NE-Hungary. It is one of the oldest nature reserves in Hungary, and its vegetation map was prepared several times, most recently in 1989. The aim of this study was to survey the actual state of the vegetation and to asses its changes during the last 15 years.Based on recent aerial photographs and field surveys a digital vegetation map was prepared for the Reserve by using geoinformatic softwares (Erdas Imagine 8.6 and ArcView GIS 3.0). Each vegetation type was given a detailed description. Phytosociological relevès were recorded in those vegetation types where such study was conducted during our previous research at the site in 1990. The most typical vegetation types are willow swamps, birch swamps, marshes, tufted sedge communities, wet and dry meadows, oak-ash-elm gallery forests, sandy pedunculate oak - silver lime forests and black locust stands. In the last 15 years vegetation succession accelerated as habitat water regime gradually became less favourable for water demanding vegetation, nutrients accumulated, and invasive species and other weeds became more abundant. As a result of these, former wet meadows of highest conservation value turned into homogenous tufted sedge communities dominated by Carex acutiformis and/or Carex riparia. These changes are unambiguously shown by the repeated phytocoenological sampling as well. The area of wet meadows decreased in this period mostly due to spontaneous forest regeneration in the absence of proper grassland management. In the shrub layer of the sandy oak forests the black locust (Robinia pseudoacacia) became dominant. No change was detected in hardwood gallery forests and in birch swamps.
Keywords: Bátorliget; vegetation mapping; nature conservation